ISU-ISU KRITIS LINGKUNGAN DAN PERSPEKTIF GLOBAL - Vania Zulfa; Milson Max; Iskar Hukum; Irfan Ilyas (Jurnal Green Growth dan Manajemen Lingkungan, 2016)
Students of the Faculty of Mathematics and Natural Sciences as part of today's society as well as part of the next generation are expected to have an in-depth understanding of environmental and ecopedagogic environmental issues because they have a supportive background to form good environmental management. With an understanding of the critical issues on the environment and the concept of ecopedagogy it is expected to open the student's perspective on how to utilize natural resources wisely so as not to cause sustained damage. The purpose of this research is to identify the relation of understanding of environmental critical issues and ecopedagogic concept with global perspective on UNJ MIPA faculty students. This research was conducted in December 2016-January 2017 at State University of Jakarta. The method used is quantitative through correlational studies. Sampling was done by simple random sampling as many as 30 students of MIPA UNJ faculty. Having tested the prerequisite, the research data is normally distributed and homogeneous. The multiple regression model is Å¶ = 74,650 -0,079X1 + 0,048X2. The correlation coefficient x1 with y is -0.177 whereas the correlation coefficient x2 with y is 0.115 with the coefficient of determination 0,013. So understanding the concept of ecopedagogic gives 1.3% contribution to global perspective. The result of this research is a negative relationship between understanding environmental critical issues with global perspective and there is a positive relationship between understanding the concept of ecopedagogic with global perspective. Therefore, by enhancing the understanding of the concept of ecopedagogic can improve the global perspective so that the environment will be maintained both for the present and for the future